Ag and IL‐2 immune complexes efficiently expand Ag‐specific Treg cells that migrate in response to chemokines and reduce localized immune responses. Issue 4 (13th January 2014) - Hamano, Ryoko; Baba, Tomohisa; Sasaki, Soichiro; Tomaru, Utano; Ishizu, Akihiro; Kawano, Mitsuhiro; Yamagishi, Masakazu; Mukaida, Naofumi
<x xml:space="preserve">Abstract</x> An intravenous administration of a high‐dose antigen (Ag) can induce immune tolerance and suppress the immune response, but the mechanism remains unclear. We recently proved that a combined i.v. administration of OVA and IL‐2‐anti‐IL‐2 Ab immune complexes (IL‐2 ICs) efficiently expands OVA‐specific Treg cells in the thymus and induces their migration into peripheral blood, by using OVA‐specific TCR Tg‐expressing DO11.10 mice. Here, we demonstrate that the expanded OVA‐specific Treg cells rapidly move into the air pouch after OVA injection in DO11.10 mice. The migration was inhibited by blocking the axis of a chemokine receptor, CCR2. Moreover, prior treatment with OVA and IL‐2 ICs enhanced OVA‐specific Treg‐cell migration and inhibited OVA‐induced delayed‐type hypersensitivity (DTH) reactions in the skin of BM chimeric mice with 15% of T cells expressing OVA‐specific TCR. Blocking the CCR2 axis reversed this suppression of DTH in these mice. Furthermore, prior treatment with OVA and IL‐2 ICs effectively reduced DTH reactions even in WT mice possessing only a very small population of OVA‐specific T cells. Thus, the treatment with Ag and IL‐2 ICs can efficiently expand Ag‐specific Treg cells with the capacity to migrate and reduce localized immune responses.